Smartboard-assisted financial literacy gamification: its impact on the engagement of children aged 5–6 years - Hanifah Aulia Yuneva; Dadan Suryana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aimed to develop a Smartboard-assisted gamified financial literacy Web-Games application and evaluate its validity, practicality, and effectiveness in improving the behavioral, emotional, and cognitive engagement of children aged 5–6 years. This Research and Development study adopted the ADDIE model. A one-group pretest–posttest design was implemented with 17 kindergarten children. Data were collected through expert validation sheets, teacher practicality questionnaires, and engagement observation sheets, and analyzed using descriptive statistics, N-Gain, and a paired-samples t-test. The media achieved highly valid (90.67%) and highly practical (90.80%) ratings. Children's engagement increased from 47.79% to 85.78%, with a significant improvement (t = 24.327, p < 0.001). The Smartboard-assisted gamified financial literacy Web-Games is a valid, practical, and effective learning medium for enhancing multidimensional engagement in early childhood learning.